Plant Stage, Not Drought Stress, Determines the Effect of Cultivars on Bacterial Community Diversity in the Rhizosphere of Broomcorn Millet (Panicum miliaceum L.) - Na, Xiaofan; Cao, Xiaoning; Ma, Caixia; Ma, Shaolan; Xu, Pengxin; Liu, Sichen; Wang, Junjie; Wang, Haigang; Chen, Ling; Qiao, Zhijun (Frontiers in Microbiology, 2019)
Broomcorn millet (Panicum miliaceum L.) is one of the oldest domesticated crops and has been grown in arid and semiarid areas in China since 10,000 cal. BP. However, limited information is available about how bacterial communities within the rhizosphere of different broomcorn millet cultivars respond to drought stress. Here, we characterized the changes in the rhizobacterial assemblages of two broomcorn millet cultivars, namely, P. miliaceum cv. HeQu Red (HQR) and P. miliaceum YanLi 10 (YL10), from the jointing stage to the grain filling stage after they were exposed to a short-term drought stress treatment at the seedling stage. Drought significantly inhibited the growth of both cultivars, but the effect on YL10 was higher than that on HQR, indicating that the drought tolerance of HQR was greater than that of YL10. Proteobacteria (33.8%), Actinobacteria (21.0%), Acidobacteria (10.7%), Bacteroidetes (8.2%), Chloroflexi (6.3%), Gemmatimonadetes (5.9%), Firmicutes (3.5%), Verrucomicrobia (2.9%), and Planctomycetes (2.7%) were the core bacterial components of broomcorn millet rhizosphere as suggested by 16S rDNA sequencing results. The diversity and composition of bacterial rhizosphere communities substantially varied at different developmental stages of broomcorn millet. As the plants matured, the richness and evenness of the rhizobacterial community significantly decreased. Principal coordinate analysis showed that the structure of the bacterial rhizosphere community changed notably only at the flowering stage between the two cultivars, suggesting a stage-dependent effect. Although drought stress had no significant effect on the diversity and structure of the bacterial rhizosphere community between the two cultivars, differential responses to drought was found in Actinobacteria and Acinetobacter, Lysobacter, Streptomyces, and Cellvibrio. The relative abundance of Actinobacteria and Lysobacter, Streptomyces, and Cellvibrio in the YL10 rhizosphere was stimulated by the drought treatment compared with that in the HQR rhizosphere, whereas the opposite effect was found in Acinetobacter. Our results suggested that the effects of cultivars on bacterial rhizosphere communities were highly dependent on plant developmental stage, reflecting the genetic variations in the two broomcorn millet cultivars.